1992
DOI: 10.1039/c39920001764
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of C60(ferrocene)2

Abstract: c6() cocrystallises with ferrocene t o give black C60(ferrocene)2, which contains discrete CEO and ferrocene molecules; the ferrocene does not reduce CeO, but the structure appears t o be stabilised as a result of weak intermolecular cha rg e-t ra nsfer i nte ractions.Buckminsterfullene (c60) is a molecular building block, which can be used to prepare new materials with interesting properties.1-3 It behaves as a mild oxidising agent, displaying six reversible one-electron reductions in solution,4 and may be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 6 publications
9
110
1
2
Order By: Relevance
“…The stable conformation of the ferrocene molecule is thus eclipsed, in agreement with the results from an early gas-phase electron-diffraction study (Haaland & Nilsson, 1968), and not staggered, as usually depicted in textbooks. The same eclipsed conformation has recently turned up in the C6o(ferrocene) 2 cocrystal (Crane, Hitchcock, Kroto, Taylor & Walton, 1992) -an unexpected corroboration! Ferrocene can thus adopt three different crystal structures.…”
Section: Polymorphism Of Ferrocenementioning
confidence: 58%
“…The stable conformation of the ferrocene molecule is thus eclipsed, in agreement with the results from an early gas-phase electron-diffraction study (Haaland & Nilsson, 1968), and not staggered, as usually depicted in textbooks. The same eclipsed conformation has recently turned up in the C6o(ferrocene) 2 cocrystal (Crane, Hitchcock, Kroto, Taylor & Walton, 1992) -an unexpected corroboration! Ferrocene can thus adopt three different crystal structures.…”
Section: Polymorphism Of Ferrocenementioning
confidence: 58%
“…Best known in this class are the alkalimetal fullerides which are already superconducting at relatively high temperatures [6]. In metal-complex fullerene cocrystallites, the interaction between the fullerene and the metal complexes is fundamentally van der Waals, such as observed in C 60 (ferrocene) 2 [7] and cocrystallates of teraarylporphyrins with C 60 [8]. Furthermore, C 60 is often described as an electron deficient polyolefin, capable of forming coordination bonds to transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…The C 60 (ferrocene-d 10 ) 2 complex [7] was prepared from C 60 (99.99%) [8] and ferrocene-d 10 [9] according to the procedure described elsewhere [2]. As a result, 95% of protons has been exchanged with deuterium in ferrocene-d 10 .…”
Section: Methodsmentioning
confidence: 99%
“…2a) is due to the two crystallographically unequivalent sites of the ferrocene in the compound. An X-ray study has reported [7], that the compound has a triclinic symmetry P1 where the C 60 molecule lies in the crystallographic inversion centre (Fig. 1).…”
Section: C Mas Nmrmentioning
confidence: 99%